Relationship between cognitive function and balance in a community-dwelling population in Japan. (4th May 2018) - Goto, Shinichi; Sasaki, Akira; Takahashi, Ippei; Mitsuhashi, Yuri; Nakaji, Shigeyuki; Matsubara, Atsushi
Abstract: Background: There has been no treatment found yet that cure dementia. Hence it is important to establish the evaluation index of cognitive decline before becoming dementia. Objective: The purpose of this study was to clarify the effective balance test indicating early cognitive decline by gender. Methods: A total of 218 volunteers (60 years of age and above) who participated in the Iwaki promotion health project in 2015 were recruited. We performed three balance tests: one leg standing test, functional reach test and static posturography, and we used mini-mental state examination (MMSE) to investigate cognitive function. Results: As a result of analysis of covariance, there was a statistically significant trend in only men that the more the MMSE score declined, the longer became the path length with both eyes opened and closed. In the result of multiple regression analysis, there was a significant negative association with MMSE score and path length with eyes opened or closed in men. There was no significant association with MMSE scores and balance tests in women. Conclusion: The study suggests that static posturography might be a useful balance test to assess early cognitive decline in men.